Evaluation of a hand carried cardiac ultrasound device in an outpatient cardiology clinic. (18th January 2005) - Vourvouri, E C; Poldermans, D; Deckers, J W; Parharidis, G E; Roelandt, J R T C
Abstract : Objective: To determine the diagnostic potential of a hand carried cardiac ultrasound (HCU) device (OptiGo, Philips Medical Systems) in a cardiology outpatient clinic and to compare the HCU diagnosis with the clinical diagnosis and diagnosis with a full featured standard echocardiography (SE) system. Methods: 300 consecutive patients took part in the study. The HCU examination was performed by an experienced echocardiographer before patients visited the cardiologist. The echocardiographer noted whether the HCU device was able to confirm or reject the referral diagnosis, which abnormality was detected, and whether SE investigation was necessary. Physical examination by a cardiologist followed and thereafter, whenever required, a complete study with an SE was carried out. The HCU data were compared with the clinical diagnosis of the cardiologist and the SE diagnosis in a blinded manner. Results: The cardiologist referred 203 of 300 patients for an SE study and 13 patients for transoesophageal echocardiography. In 84 patients no further examination was considered necessary. HCU echocardiography was able to confirm or reject the suspected clinical diagnosis in 159 of 203 (78%) patients. In 44 of 203 (22%) patients SE Doppler was needed. Agreement between the HCU device and the SE system for the detection of major abnormalities was excellent (98%). The HCU device missed 4% of the major findings. Among the 84 patients not referred for an SE, the HCU device detected unsuspected major abnormalities missed with the physical examination in 14 (17%). Conclusion: Integration of an HCU device with the physical examination augments the yield of information.